Is logistically motivated ex vivo lung perfusion a good idea? - Van De Wauwer, Caroline; van Suylen, Vincent; Zhang, Zhang L.; Verschuuren, Erik A. M.; van der Bij, Wim; Gan, C. Tji; Ubbink, Rinse; Erasmus, Michiel E. (Frontiers in Transplantation, 2022)
Ex vivo lung perfusion (EVLP) is a technique for reconditioning and evaluating lungs. However, the use of EVLP for logistical reasons is still under discussion. In this retrospective study, all EVLPs performed between July 2012 and October 2019 were analyzed for ventilation and perfusion data. After transplantation, primary graft dysfunction (PGD), lung function, chronic lung allograft dysfunction (CLAD)-free survival, and overall survival were analyzed. Fifty EVLPs were performed: seventeen logistic EVLPs led to 15 lung transplantations (LT) and two rejections (LR), and 33 medical EVLPs resulted in 26 lung transplantations (MT) and seven rejections (MR). Pre-EVLP PaO2 was lower for MT than LT (p < 0.05). Dynamic lung compliance remained stable in MT and LT but decreased in MR and LR. Plateau airway pressure started at a higher level in MR (p < 0.05 MT vs. MR at T60) and increased further in LR. After transplantation, there were no differences between MT and LT in PGD, lung function, CLAD-free survival, and overall survival. In addition, the LT group was compared with a cohort group receiving standard donor lungs without EVLP (LTx). There were no significant differences between LT and LTx for PGD, CLAD-free survival, and overall survival. FVC was significantly lower in LT than in LTx after 1 year (p = 0.005). We found that LT lungs appear to perform better than MT lungs on EVLP. In turn, the outcome in the LT group was comparable with the LTx group. Overall, lung transplantation after EVLP for logistic reasons is safe and makes transplantation timing controllable.